2018
DOI: 10.1063/1.5020563
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial ion solvation: Obtaining the thermodynamic limit from molecular simulations

Abstract: Inferring properties of macroscopic solutions from molecular simulations is complicated by the limited size of systems that can be feasibly examined with a computer. When long-ranged electrostatic interactions are involved, the resulting finite size effects can be substantial and may attenuate very slowly with increasing system size, as shown by previous work on dilute ions in bulk aqueous solution. Here we examine corrections for such effects, with an emphasis on solvation near interfaces. Our central assumpt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 124 publications
4
38
0
Order By: Relevance
“…Both cases are shown in Figure 2b, which shows that inclusion of distant boundaries, both Bethe and physical boundaries, oppose the usual charge hydration asymmetry in the case of SPC/E-like water models because both ∆v q C and (∆v q C + ∆v q D ) are negative. This is in agreement with recent results from Cox and Geissler, who computed ionic charging free energies in systems with and without an explicit water-vapor interface, and showed that proper inclusion of the boundary potentials, as well as important system size and geometry-dependent dielectric response corrections, bring the two sets of free energies into agreement 57 .…”
Section: Implications For Ions With Excluded Volume Coressupporting
confidence: 92%
See 1 more Smart Citation
“…Both cases are shown in Figure 2b, which shows that inclusion of distant boundaries, both Bethe and physical boundaries, oppose the usual charge hydration asymmetry in the case of SPC/E-like water models because both ∆v q C and (∆v q C + ∆v q D ) are negative. This is in agreement with recent results from Cox and Geissler, who computed ionic charging free energies in systems with and without an explicit water-vapor interface, and showed that proper inclusion of the boundary potentials, as well as important system size and geometry-dependent dielectric response corrections, bring the two sets of free energies into agreement 57 .…”
Section: Implications For Ions With Excluded Volume Coressupporting
confidence: 92%
“…Periodic boundaries result in an ionic charging free energy that arises purely from local structural perturbations, both charging induced, ∆G c IS , and from any local core contributions to ρ q 0 (r) that may contribute to ∆G c PB . Note that PBCs may lead to additional finite size effects on ∆G c IS that have been discussed throughout the literature 50,53,56,57 , and we ignore these well understood corrections.…”
Section: A Site-based Periodic Boundariesmentioning
confidence: 99%
“…Even so, Cox and Geissler have shown that dielectric continuum descriptions can provide highly accurate finite size corrections for ion solvation at planar interfaces. 57 Together these results make clear that the key is to unravel the local and non-linear electrostatic effects through explicit atomistic or variable density representations, that is then embedded in or corrected by a continuum model for the long-range electrostatic effects. This is likely why modified Poisson Boltzmann treatments/DFT 58 and classical/quantum DFT approaches 56 and recent hybrid and double hybrid functionals which incorporate some percentage of exact exchange, are addressing better QM accuracy 61 , and new approaches have been introduced that incorporate true many-body polarization effects across the QM/MM boundary.…”
Section: Summary and Future Directionsmentioning
confidence: 91%
“…Contrary to Born's result, computer simulations indicate that the sign of the charge of small ions can signicantly inuence their charging free energy F chg (q, R), i.e., the work involved in reversibly introducing the solute's charge q. [30][31][32][33][34][35][36][37][38][39] This dependence is most easily scrutinized for simple point charge (SPC) models of molecular interactions, where an ion's charge can be varied independently of its other properties. In SPC/E water, 40 for instance, charging a solute roughly the size of uoride (R F z 0.317 nm) has an asymmetry, F chg (e, R F ) À F chg (Àe, R F ) z 16 kcal mol À1 , almost 30 times larger than thermal energy k B T. Here, e is the magnitude of an electron's charge.…”
Section: Distant Interfaces and The Neutral Cavity Potentialmentioning
confidence: 87%